ANALISIS MANAJEMEN RISIKO DALAM PEMBIAYAAN MURABAHAH DI KOPERASI KELUARGA KESEHATAN SYARIAH JAMBI - Maula, Nikmatul; Kurniawan, Bambang; Saputra Siregar, Erwin (Universitas Sains dan Teknologi Komputer, 2024)
Basically risk management includes activities to plan, organize, lead, coordinate, and supervise risk management programs. Financing is one of the activies, including the Jambi Syariah Health Family Cooperative. And at the time of doing the financing of course will not be separated from the name of risk. So cooperatives need to implement risk management in order to be able to minimize the possibility of risks that will occur at some point in time. The purpose pf this research is to find out how to apply risk management to murabahah financing in the Jambi Syari’ah Health Fsmily Cooperatives. The type of research used is field (field research). This research is descriptive, namely research that tries to determine the solution to the current problem based on the data. The types and sources of data used in the research are primary and secondary data. Data collection techniques using observation, interviews and documentation. To check the validity is to use triangulation of sources and reference materials is used. The method consists of three stages, namely data reduction, data presentation, and data verification. The result of the research carried out are the application of risk management murabahah financing at the Jambi Sharia Health Family Cooperative has bee carried out correctly by using a referral pr referensi system,surveyor scoring, useof goods, guarantees, committee meetings, reserves for earning assets write-of (PPAP), and make the remainingoperating results (SHU). Although the implementation of financing risk management has been carried out properly. But whose name is risk cannot be eliminated can minimize it.